CLINICAL AND LABORATORY FEATURES OF THE BLOOD COAGULATION SYSTEM IN PATIENTS WITH CIRRHOSIS OF THE LIVER ASSOCIATED WITH VIRAL HEPATITIS B, C AND D (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Viral hepatitis is one of the most urgent problems of modern medicine and healthcare. According to WHO, more than 50 million people are infected with viral hepatitis every year [2, 6]. Of these, more than 10% develop chronic viral hepatitis (HCV). In 20% of cases, the outcome of HCV is cirrhosis, and in 5% - hepatocellular carcinoma (HCC) of the liver, which determines high levels of mortality and mortality [1, 2, 6]. Viral liver cirrhosis (CP) is one of the final stages of the morphogenesis of chronic viral hepatitis.